2023
DOI: 10.1007/s12672-023-00627-0
|View full text |Cite
|
Sign up to set email alerts
|

MUC1 promotes lung metastases of liver cancer by impairing anti-tumor immunity

Abstract: Purpose MUC1 is a membrane bound protein that can regulate tumor progression but its role in tumor metastasis and the metastatic microenvironment remains unclear. Methods We performed differential gene analysis for primary liver cancer (n = 31) and lung metastases (n = 31) using the Gene Expression Omnibus (GEO) dataset (GSE141016) and obtained RNA sequencing data from 374 liver cancer and 50 normal tissues from The Cancer Genome Atlas (TCGA). We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Notably, a cluster of genes associated with early cancer initiation and progression, including MYC, CD44, ALDH4A1, MUC1, GPC3 and GPC4 exhibited signi cantly elevated expression levels in TP53KO-eHEPOs. Due to the wide acceptance of these markers in the initiation of liver cancer and their high expression in various other cancers, they hold potential as therapeutic targets [45][46][47][48]. The implications of these ndings are further substantiated by previous research.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Notably, a cluster of genes associated with early cancer initiation and progression, including MYC, CD44, ALDH4A1, MUC1, GPC3 and GPC4 exhibited signi cantly elevated expression levels in TP53KO-eHEPOs. Due to the wide acceptance of these markers in the initiation of liver cancer and their high expression in various other cancers, they hold potential as therapeutic targets [45][46][47][48]. The implications of these ndings are further substantiated by previous research.…”
Section: Discussionmentioning
confidence: 85%
“…To explore the role of TP53KO-eHEPOs in liver cancer initiation and progression, we examined several well-conserved markers in our transcriptome dataset. We observed an increased signal in TP53KO-eHEPOs for tumorigenesis markers associated with cancer initiation and/or progression, including CD44, MYC, MUC1, and CD36 [45][46][47][48] (Fig. 3E).…”
Section: Early Liver Cancer Initiation Markers Enriched In Tp53ko-eheposmentioning
confidence: 99%
“…), which was consistent with other research results. 39,40 However, when the lanthanide luminescence probe system was applied to detect plasma samples that do not exhibit high-levels of co-expression of EpCAM and MUC1 antigens on sEVs only the fluorescence signals at the same level as those found in the healthy control group can be detected. These results indicated that our AND gate photoluminescence strategy can be applied to detect plasma samples with expression of both sEVs' EpCAM and MUC1, to reveal the existence of the epithelial cancers accurately.…”
Section: Quantification Of Epithelial Breast Cancer Sevs' Epcam and M...mentioning
confidence: 99%